Are we living in a post‐Basel world?. Issue 1 (11th December 2014) - Lepawsky, Josh
<x xml:space="preserve">Abstract</x> The Basel Convention (the Convention) is a key piece of law governing the international waste trade. The spirit of the Convention is to prohibit the dumping of hazardous waste from 'developed' countries to 'developing' countries. Yet, a careful consideration of the Convention suggests a problematic geographical imaginary at work in it. It imagines a bi‐modal world comprised of what it calls Annex VII countries (Organization for Economic Cooperation and Development (OECD), the European Community (EC) and Lichtenstein) and non‐Annex VII countries (all other signatories) and seeks to prohibit the shipment of hazardous waste from the former to the latter. In effect, what this geographical imaginary attempts to institute is a world of trade in which all non‐Annex VII territories are equally vulnerable to hazardous waste dumping from Annex VII territories, but not vulnerable to such dumping amongst themselves. Yet, the non‐Annex VII grouping contains a hugely diverse set of countries, including the two largest non‐Annex VII economies, China and India. Drawing on textual analysis of Convention documents and trade data available for China and India, the paper engages with recent research into the growing role of 'South–South' trade to critically engage with the geographical imaginary of the Basel Convention. It suggests that as the global patterns of hazardous waste trade shift, the relevance of the Basel Convention's geographical imaginary declines.